2022
DOI: 10.3390/jcdd9030084
|View full text |Cite
|
Sign up to set email alerts
|

Gender Particularities and Prevalence of Atypical Clinical Presentation in Non-ST Elevation Acute Coronary Syndrome

Abstract: Clinical presentation is one of the factors that can influence how quickly a patient with an acute coronary syndrome is treated, particularly if it is atypical. The purposes of this study are to explore gender-related differences in patients presenting with non-ST elevation acute coronary syndromes (NSTEACS) from the perspective of a series of common risk factors as well as treatment strategies and to evaluate the prevalence of atypical clinical presentation of NSTEACS in the study group. In addition, we explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The present study, similar to previous studies (1, 10, 18), showed that FH, DLP, Smoking, and male gender increase the incidence of CAD and decrease the age of occurrence. It seems that the reason for the increase in the age of the disease in hypertensive patients is the following: a) The average age of hypertensive patients in this study was higher than the average age of the onset of the disease (23-25), b) Hypertensive patients experience chest pain more atypically and therefore refer for angiography later (26) c) Hypertensive patients become symptomatic later due to the formation of coronary collateral vessels and therefore refer to angiography later (27,28), and d) Hypertensive patients receive more primary prevention strategies (23). In this study, diabetes also slightly and insigni cantly increased the age of onset of the disease, and the above reasons also apply to diabetic patients.…”
Section: Resultsmentioning
confidence: 73%
“…The present study, similar to previous studies (1, 10, 18), showed that FH, DLP, Smoking, and male gender increase the incidence of CAD and decrease the age of occurrence. It seems that the reason for the increase in the age of the disease in hypertensive patients is the following: a) The average age of hypertensive patients in this study was higher than the average age of the onset of the disease (23-25), b) Hypertensive patients experience chest pain more atypically and therefore refer for angiography later (26) c) Hypertensive patients become symptomatic later due to the formation of coronary collateral vessels and therefore refer to angiography later (27,28), and d) Hypertensive patients receive more primary prevention strategies (23). In this study, diabetes also slightly and insigni cantly increased the age of onset of the disease, and the above reasons also apply to diabetic patients.…”
Section: Resultsmentioning
confidence: 73%
“…Typical symptoms of CAD include central oppressive chest pain, jaw and left arm pain, diaphoresis, shortness of breath, nausea, and vomiting [5][6][7][8][9][10]. Atypical symptoms include fatigue, epigastric pain, dull or burning pain, palpitations, lightheadedness, neck pain, indigestion, shoulder pain, right arm pain, back pain, dizziness, or even syncope.…”
Section: Introductionmentioning
confidence: 99%
“…Atypical symptoms include fatigue, epigastric pain, dull or burning pain, palpitations, lightheadedness, neck pain, indigestion, shoulder pain, right arm pain, back pain, dizziness, or even syncope. Atypical symptoms are more prevalent in women and diabetic patients, and these symptoms are usually overlooked by healthcare providers [5][6][7][8][9][10][11][12]. A study suggests that labeling symptoms as 'typical' or 'atypical' should no longer be done as the presentation of CAD varies with age, sex, race, and other preexisting risk factors [8].…”
Section: Introductionmentioning
confidence: 99%
“…ACS presentation can be due to microvascular disease or plaque rupture in women [ 16 ]. Spontaneous coronary artery dissection is a particular morbid form of ACS associated with arteriopathies, and is most common late in pregnancy or postpartum [ 17 , 18 ].…”
mentioning
confidence: 99%